KARAKTERISTIK MORFOMETRIK DAN MERISTIC LIMA JENIS IKAN BADUT (Amphiprion sp.) DARI PULAU AMBON - Helena Afia Sahusilawane; Dinar Tri Soelistyowati (Jurnal Perikanan Unram, 2021)
Amphiprion is one of the genera in the Pomacentridae family which is dominant on coral reefs in the waters of Ambon Island. This fish has interesting morphological characteristics, unique reproductive behavior, and has a symbiosis with sea anemones as a host and has high adaptability in captivity. The diversity of species in the genus Amphiprion is high based on varying morphological characters. The purpose of this study was to characterize the morphometric and meristic characters of five types of clown fish (Amphiprion sp.) from the island of Ambon. The morphometric characteristics were measured by measuring 24 characters, while the meristic characteristics were calculated using 5 characters in parent fish Amphiprion clarkii, A. frenatus, A. ocellaris, A. percula, and A. sandaracinos which had been kept for 1 year at the Ambon Marine Aquaculture Center. The data of morphometric and meristic characteristics were evaluated using principal component analysis (PCA). The relationship between individuals was analyzed using genetic distance based on the UPGMA program from PAST software. The results of PCA analysis showed differences in morphometric characters and the five types of clownfish formed two main clusters, the first cluster consisted of A. ocellaris and A. percula and A. sandaracinos, and the second cluster consisted of A. clarkii and A. frenatus. This clustering can provide information for breeders and cultivators in the development of clown fish cultivation in breeding programs.